2016
DOI: 10.5194/amt-9-2103-2016
|View full text |Cite
|
Sign up to set email alerts
|

Ash and ice clouds during the Mt Kelud February 2014 eruption as interpreted from IASI and AVHRR/3 observations

Abstract: Abstract. During the Mt Kelud February 2014 eruption the ash cloud was detectable on 13-14 February in the infrared with the reverse absorption technique by, for example, the Advanced Very High Resolution Radiometer (AVHRR/3). The Infrared Atmospheric Sounding Interferometer (IASI) observed the ash cloud also on 15 February when AVHRR did not detect any ash signal. The differences between ash detection with AVHRR/3 and IASI are discussed along with the reasons for the differences, supported by radiative transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Kelut, located in Java, Indonesia (7.93°S, 112.31°E, 1.73‐km summit elevation), erupted at approximately 1600 universal time coordinated (UTC) on 13 February 2014 (Kylling, ). The Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument aboard Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (Winker et al, ; Winker et al, ), which made an overpass over the region at around 13/1800 UTC, revealed the ash to consist of a broad region associated with the umbrella cloud reaching to a maximum altitude of about 19 km and a core region reaching to a maximum altitude of about 25 km.…”
Section: Verification Resultsmentioning
confidence: 99%
“…Kelut, located in Java, Indonesia (7.93°S, 112.31°E, 1.73‐km summit elevation), erupted at approximately 1600 universal time coordinated (UTC) on 13 February 2014 (Kylling, ). The Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument aboard Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observations (Winker et al, ; Winker et al, ), which made an overpass over the region at around 13/1800 UTC, revealed the ash to consist of a broad region associated with the umbrella cloud reaching to a maximum altitude of about 19 km and a core region reaching to a maximum altitude of about 25 km.…”
Section: Verification Resultsmentioning
confidence: 99%
“…Kelut, located in Java, Indonesia (7.93°S, 112.31°E, 1.73 km summit elevation), erupted at approximately 1600 UTC on 13 February 2014 [ Kylling , ]. The Darwin VAAC initially estimated the maximum height of the ash cloud to be at Flight Level 450 (13.7 km) based on the MTSAT image at 1632 UTC on 13 February (Figure a) and later revised this to Flight Level 550 (16.7 km) based on the 2232 UTC on 13 February image (Figure c) several hours later.…”
Section: Some Case Studiesmentioning
confidence: 99%
“…Kelut, located in Java, Indonesia (7.93°S, 112.31°E, 1.73 km summit elevation), erupted at approximately 1600 UTC on 13 February 2014 [ Kylling , ]. The event was well covered by numerous satellite instruments including the airborne lidar (Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP)) on board CALIPSO [ Winker et al , ].…”
Section: Some Case Studiesmentioning
confidence: 99%